Multivariable calculus - Stewart, James (Brooks/Cole, 1999)
A reprinting of the multivariable portion of "Calculus, Fourth Edition". These reproduced chapters cover: vectors and the geometry of space, vector functions, partial derivatives, multiple integrals, vector calculus, and second-order differential equations. These chapters are a direct continuation of "Single Variable Calculus, Fourth Edition" and "Single Variable Calculus, Early Transcendentals, Fourth Edition". Particularly important results from single variable calculus are summarized for at-a-glance review.